The Prospects for the Development of Souraja Cultural Heritage Area for Community-Based Tourism Development, Palu City - Harifuddin Thahir; Irdinal Arief; Noor Riefma Hidayah; Suci Amalia Namira (JCOMENT (Journal of Community Empowerment), 2023)
Community-based tourism can create employment opportunities for local communities and reduce poverty, were tourism revenues from tourism service. In the development of facilities and infrastructure needed by the development prospects, apart from being a tourist object, the community plays a role in its development and is integrated with the surrounding environment. The thing of tourism is in the form of cultural heritage buildings located in urban areas so that this becomes integrated with the local community and the Government. This happened in Palu City, but a natural disaster (earthquake, liquefaction and tsunami) occurred on 2018 which resulted in damage some buildings, one of which was the Souraja traditional house located in Kampung Lere, Palu. The "Souraja" Traditional House is one of the physical remains of the cultural heritage of the past ancestors, namely the Kingdom of Palu, which was founded in 1892. After the disaster, the Souraja cultural heritage will be rehabilitated. Still, it will also revitalize the area because since long ago, the people of Kampung Lere, who are local people from the environment around Souraja, have wanted to be fully involved in developing and reviving Kampung Lere to be better known in urban cultural tourism which has past historical values of the Kaili tribe on the coast of Palu City. The finding is that the prospect of development will be an opportunity to revive the environmental area around Souraja for the Kampung Lere community to develop urban tourism with the Souraja cultural heritage as a regional landmark.